2012
DOI: 10.1371/journal.pone.0030945
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against Leishmania major Infection Using LACK- and IL-12-Expressing Lactococcus lactis Induces Delay in Footpad Swelling

Abstract: Background Leishmania is a mammalian parasite affecting over 12 million individuals worldwide. Current treatments are expensive, cause severe side effects, and emerging drug resistance has been reported. Vaccination is the most cost-effective means to control infectious disease but currently there is no vaccine available against Leishmaniasis. Lactococcus lactis is a non-pathogenic, non-colonizing Gram-positive lactic acid bacterium commonly used in the dairy industry. Recently, L. lactis was used to express b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…After oral administration, only the strain secreting the antigen and co-expressing IL-12 induced protection against the parasite [105]. In another study these same authors showed that subcutaneous co-administration of L. lactis secreting IL-12 with either a strain secreting LACK or a strain with a cell wall anchored (CWA)-LACK led to induction of protective immunity [106]. The lack of effectiveness of the CWA-LACK strain in oral immunization could be due to the fact that the expression strain was an alr mutant, which could lead to impaired cell-wall strength and, possibly, antigen anchoring.…”
Section: Lab Displaying Antigensmentioning
confidence: 97%
“…After oral administration, only the strain secreting the antigen and co-expressing IL-12 induced protection against the parasite [105]. In another study these same authors showed that subcutaneous co-administration of L. lactis secreting IL-12 with either a strain secreting LACK or a strain with a cell wall anchored (CWA)-LACK led to induction of protective immunity [106]. The lack of effectiveness of the CWA-LACK strain in oral immunization could be due to the fact that the expression strain was an alr mutant, which could lead to impaired cell-wall strength and, possibly, antigen anchoring.…”
Section: Lab Displaying Antigensmentioning
confidence: 97%
“…Subcutaneous immunization with L. lactis expressing the cell wall–anchored form of A2 induced the higher levels of antigen‐specific serum antibodies, while mice immunized with L. lactis producing the cytoplasmic form of A2 demonstrated the highest reduction in liver parasitemia after visceral L. donovani challenge. Later, the same group reported the construction of different lactococci strains expressing one of the best‐studied Leishmania major antigens, the Leishmania homologue of activated C kinase (LACK), in the cytoplasmic, secreted, or cell wall–anchored forms, and a strain secreting biologically active mouse IL‐12 (Hugentobler et al ., , b). Subcutaneous co‐immunization with live L. lactis strains expressing the cell wall–anchored form of LACK and secreting IL‐12 significantly delayed footpad swelling in L. major ‐infected mice.…”
Section: Use Of L Lactis As Live Delivery Vectormentioning
confidence: 99%
“…Furthermore, immunization with these two strains induced antigen‐specific multifunctional TH1 CD4 + and CD8 + T cells and a systemic LACK‐specific TH1 immune response. This same group then evaluated the effect against L. major infection in mice after oral immunization with recombinant L. lactis strains deficient in alanine racemase (alr‐), an enzyme that participates in cell wall synthesis (Grangette et al ., ), expressing LACK antigen in the cytoplasmic, secreted, or cell wall–anchored forms alone or in combination with a L. lactis strain secreting mouse IL‐12 (Hugentobler et al ., , b). They showed that oral immunization using live lactococci secreting both LACK and IL‐12 was the only treatment that partially protected the mice against subsequent L. major challenge.…”
Section: Use Of L Lactis As Live Delivery Vectormentioning
confidence: 99%
“…85,86 Consistent with this concept, inclusion of IL-12 as part of a DNA vaccine cocktail improved protection against L major challenge. [87][88][89] However, administration of IL-12 in humans is toxic; thus, this strategy is not suitable for human vaccination. 90,91 Several studies have demonstrated that complete clearance of the parasite by a T H 1 immune response, which is desirable for the safety of a patient, is, however, not sufficient in mediating long-term immunity.…”
mentioning
confidence: 99%